Brain Resting-State Network Alterations Associated With Crohn's Disease - Kornelsen, Jennifer; Wilson, Alyssia; Labus, Jennifer S.; Witges, Kelcie; Mayer, Emeran A.; Bernstein, Charles N. (Frontiers in Neurology, 2020)
Inflammatory bowel disease (IBD) is a chronic disease that is associated with aspects of brain anatomy and activity. In this preliminary MRI study, we investigated differences in brain structure and in functional connectivity (FC) of brain regions in 35 participants with Crohn’s disease (CD) and 21 healthy controls (HC). Voxel based morphometry (VBM) analysis was performed to contrast CD and HC structural images. Region of interest (ROI) analyses were run to assess functional connectivity (FC) for resting state network nodes. Independent component analysis (ICA) identified whole brain differences in functional connectivity associated with resting state networks. Though no structural differences were found, ROI analyses showed increased FC between the frontoparietal (FP) network and salience network (SN), and decreased FC between nodes of the default mode network (DMN). ICA results revealed changes involving cerebellar (CER), visual (VIS), and SN components. Differences in FC associated with sex were observed for both ROI and ICA analyses. Taken together, these changes are consistent with an influence of CD on the brain and serve to direct future research hypotheses.